State Institute of Islamic Religion - Aldiansyah Aldiansyah; Abd Mukti; Sapri Sapri (Universitas Muhammadiyah Enrekang, 2024)
This scientific study aims to analyze in more depth the institutional and educational system of PTAIN, especially IAIN. This scientific study uses qualitative research methods with the type of library research. The data used in this study is secondary data, including various government policies (UU, PP, Presidential Decree, or Ministerial Regulation), journals, and books that are appropriate to the topic to be studied. The results of the analysis state that institutionally, IAIN has been recognized and even has similarities and equality with other state higher education institutions. Starting from the organizational structure, to the government policies that cover it (PP No. 30, 1990). However, IAIN is within the Ministry of Religion, not the Ministry of Education and Culture. Apart from that, in the education system, IAIN refers to the applicable National Education System (UU No. 20/2003). However, the specific IAIN policy will be disclosed in the Regulation of the Minister of Religion in each relevant IAIN Statute.